PENGARUH KEAHLIAN, INDEPENDENSI DAN KEMAHIRAN PROFESIONAL TERHADAP KUALITAS HASIL PEMERIKSAAN DENGAN PENGALAMAN KERJA SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA INSPEKTORAT KOTA PEKANBARU DAN KOTA DUMAI) - Amelia Bettry Fermana; Hardi Hardi; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was demonstrate the influence of expertise, independence and professional skills on the quality of the result and the effect of work experience on relation expertise, independence and professional skills with the quality of inspection result. This study is a survey with census method, while spreading technique using questionnaires distributed to inspectors Inspectorate Pekanbaru Cityy and Dumai City. Of the 60 questionnaires distributed, 52 questionnaires were returned. Data analysis was performed by multiple linear regression testing and MRA. The result showed partially expertise, independence and professional skills on the quality of the result. Job experience as a moderating variable proved to be able to strengthen the relationship between expertise, independence and professional skills on the quality of inspection result.Keywords: Expertise, Independence, Professional Skills, Work Experience, and Quality Inspection Result.